Role of Hygiene, Sanitation and Behavior Handler Food with Existence Bacteria Escherichia coli in Children’s Snacks in Elementary Schools and Madrasah Ibtidaiyah (MI) - Cucu Herawati; Heni Endayani; Suzana Indragiri; Iin Kristanti; Supriatin; Nuniek Tri Wahyuni; Awis Hamid Dani; Isna Hikmawati (Recent Updates in Disease and Health Research Vol. 7, 2024)
Food is a basic human need that requires good management to prevent it as a medium for disease transmission. Street snacks are a source of bacterial contamination, and many snacks do not meet health requirements. Therefore, this study aimed to analyze the role of sanitation hygiene and food handlers’ behavior in the occurrence of Escherichia coli contamination in food served to children at elementary schools and Madrasah Ibtidaiyah (MI). This study employed an analytical survey method with a cross-sectional design. A population consisting of 78 individuals selling children’s food during the January 2023 period was used for the study. The sample consisted of 43 food vendors, selected using purposive sampling. The inclusion criteria were respondents who sell food in Elementary Schools and MI, while the exclusion criteria were those who sell covered or packaged food. Data were collected through observation sheets and interviews. Data analysis involved both univariate and bivariate methods using the Chi-Square test. The results showed that 31 respondents (72.1%) adhered to sanitary hygiene requirements, 33 respondents (76.7%) fulfilled the criteria for food handlers’ behaviour, and nine respondents (20.9%) had their food contaminated with Escherichia coli. Of the 43 food samples studied, more than half (65.1%) were snacks. A relationship exists between sanitation hygiene and Escherichia coli contamination in children’s food in Elementary Schools and MI (p-value = 0.0001). Additionally, a relationship was observed between food handlers’ behaviour and Escherichia coli contamination in food served at both types of schools (p-value = 0.0001). There was no relationship between the kind of food and Escherichia Coli contamination in children’s snacks, p = 0.615. These results emphasized the importance of street food vendors consistently prioritizing and implementing proper food sanitation, hygiene and healthy practices. This method was crucial to prevent Escherichia coli contamination and ensure the safety of food served to children.